Foreign Nurses and Hospital Quality: Evidence from Brexit - Henrique Castro-Pires; Marco Mello; Giuseppe Moscelli (Institute of Labor Economics (IZA), 2023)
We exploit the 2016 Brexit referendum as a migration shock to evaluate the impact of reduced labour supply on the provision of hospital care. After the referendum, a sharp drop in the number of early-career new joiners from Europe resulted in a considerable decrease in the share of EU nurses in the English NHS. Using an enclave instrumental variable empirical strategy, we find that emergency readmission rates increased, and more so in hospital organizations more exposed to the missing inflow of new joiners. A theoretical model shows that this is consistent with a decrease in the quality of new hires.
Keywords: J45; J61; J68; I11; C26; 330; labour supply; workers' mobility; immigration; patient care; hospital quality; Brexit